A Case Study On Kellogg - Khazaei, Mehdi (2007)
Kellogg Company is the world's leading producer of cereal and a leasing producer of convenience foods, including cookies, crackers, toasters pastreies, cereal bars, fruit snacks, frozen waffles and veggie foods.